The Influence of Statisfaction on Visit Intention Through Visitor Loyalty at Taman Impian Jaya Ancol, Jakarta, Indonesia - Linda Desafitri Ratu Bilqis; Chairul Salim; Faiza Rachim; Adiwiyah, Robiantul; Pramudito (Jurnal Ilmiah Hospitality Management, 2025)
The decline in post-pandemic visitor numbers at Taman Impian Jaya Ancol calls for strategies to rebuild public interest in visiting. This study aims to analyze the effect of visitor satisfaction on revisit intention, with loyalty as a mediating variable. A quantitative approach was employed through a survey of 200 respondents who had visited Ancol in the past 12 months. Data were analyzed using SmartPLS to assess validity, reliability, and both direct and indirect relationships between variables. The results indicate that satisfaction significantly influences loyalty and revisit intention, both directly and through loyalty as a mediator. These findings highlight the importance of delivering a comprehensive visitor experience, not only in service quality but also in fostering emotional attachment. The practical implication suggests that visitor retention strategies should focus on strengthening loyalty to enhance sustainable visits to urban tourism destinations.